State Labor Relations Acts - Doan, Mason C. (Quarterly Journal of Economics, 1942)
Introduction, 507. — State acts modeled on the National Act: fundamental provisions, 508; peculiar details, 510; jurisdiction, 512. — Operation of the boards under these acts: Utah, 513; Massachusetts, 514; Pennsylvania, 517; New York, 518; Wisconsin, 525; Rhode Island, 532. — The acts of 1938 and 1939 and the amendments of 1939: the change of trend, 532; Oregon, 534; Michigan, 536; Minnesota, 538; Pennsylvania, 542; Wisconsin, 545. — Conclusions, 556.